Temporal and Spatial Analysis of the Impact of the 2015 St. Patrick’s Day Geomagnetic Storm on Ionospheric TEC Gradients and GNSS Positioning in China Using GIX and ROTI Indices - Zhihao Fu; Ningbo Wang; Xuhui Shen; Ang Li (Remote Sensing, 2025)
Geomagnetic storms induce ionospheric disturbances, significantly affecting Global Navigation Satellite System (GNSS) positioning accuracy. This study investigates how geomagnetic storm-induced ionospheric irregularities influence GNSS Precise Point Positioning (PPP), using data from approximately 260 GNSS stations across China during 15 storm events between 1 January and 30 June 2015. We applied two indices—the Gradient Ionosphere Index (GIX), representing spatial gradients of vertical total electron content (VTEC), and the Rate of TEC Index (ROTI), describing temporal TEC variations. The analysis identified the St. Patrick’s Day geomagnetic storm (17 March 2015) as causing the most pronounced ionospheric disruptions, with significant east–west TEC gradients (|GIXx,P95| > 50 mTECU/km) consistently associated with substantial PPP errors (>0.5 m). Spatial analyses further indicated that significant 3D PPP errors (PPP, P95 > 0.4 m) closely overlapped with regions experiencing intense east–west TEC gradients, predominantly in the 20–35°N latitude band. Further analysis indicated notable pre-storm ionospheric enhancements driven by zonal electric fields, distinct ionospheric suppression associated with westward disturbance dynamo electric fields (DDEFs) on 18 March, and re-intensification due to eastward penetration electric fields (PEFs) on 19 March.